Pengelolaan Surat Masuk Dan Surat Keluar di Sekretariat Daerah Kabupaten Solok Selatan - Kisma, Hepri; Yohanis (LPPM STISIP IMAM BONJOL, 2024)
The purpose of this study was to find out the implementation of incoming and outgoing mail management, as well as the obstacles that arise in managing incoming and outgoing mail at the Administrative Office of the General Section of the Regional Secretariat of South Solok Regency. This research is a descriptive research with a qualitative approach. Data collection techniques used are observation, documentation and interviews. Test the validity of the data using source triangulation. The data analysis technique used is an interactive technique, which consists of: data reduction, data presentation, and drawing conclusions. The results of this study indicate that management of letters in the Administrative Office of the General Section of the Regional Secretariat of Solok Selatan Regency has not been implemented optimally, namely 1) The use of mail management equipment has not been optimal. 2) Retrieval of archives is less than optimal. 3) No special action has been taken to maintain the existing archives. 4) There is no officer who handles archives. 6) There is no awareness among employees at the Administrative Office of the General Section of the Regional Secretariat of Solok Selatan Regency about archive management